2023
DOI: 10.1002/rmv.2428
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of rapid antigen tests in comparison to RT‐PCR for SARS‐COV‐2 diagnosis in Omicron variant: A systematic review and meta‐analysis

Abstract: The Omicron variant of concern has a high level of mutations in different genes that has raised awareness about the performance of immunological products such as vaccines and antigen detection kits. In this systematic review and meta-analysis, we investigated whether Omicron had a significant influence on rapid antigen test (RAT) performance in comparison to PCR. We registered this systematic review and meta-analysis in PROSPERO with the registration number CRD42022355510. We searched PubMed, Scopus, Embase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
(84 reference statements)
0
19
0
Order By: Relevance
“…All other RADTs evaluated in this study showed no significant change in test performance against Omicron variants. Previous studies evaluating RADTs have consistently reported similar or reduced clinical sensitivity with Omicron as compared to early pandemic variants (21, 37, 39). For example, multiple studies investigating the Abbott Panbio using cultured virus (40) and clinical samples (23, 41) have shown no sensitivity loss against Omicron.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…All other RADTs evaluated in this study showed no significant change in test performance against Omicron variants. Previous studies evaluating RADTs have consistently reported similar or reduced clinical sensitivity with Omicron as compared to early pandemic variants (21, 37, 39). For example, multiple studies investigating the Abbott Panbio using cultured virus (40) and clinical samples (23, 41) have shown no sensitivity loss against Omicron.…”
Section: Discussionmentioning
confidence: 84%
“…A meta-analysis by Mohammadie et al (37) on RADT performance revealed a pooled sensitivity of 67% and a non-significant reduction in overall RADT sensitivity against Omicron. While these general trends provide valuable insights into overall RADT performance, the diversity of targets needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…After the thorough abolishment of the dynamic zero-COVID-19 policy, there was no large-scale nucleic acid testing any more, and COVID-19 rapid antigen test (RAT) kits were primary tools for COVID-19 testing. 10 The secondary means of COVID-19 testing was self-paying nucleic acid testing at hospital. In the absence of the two COVID-19 testing means, it seemed unreasonable to make a diagnosis of COVID-19 via symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] Reverse transcriptase polymerase chain reaction (RT-PCR) is considered the gold standard method, and several RT-PCR approaches for viral detection have been reported. [8][9][10] However, RT-PCR has a long turnaround time and requires an expensive thermal cycler, which is a bottleneck in resource-limited settings. [11] An alternative technique, loop-mediated isothermal amplification (LAMP) has emerged as a simple, sensitive, and low-cost means for amplification.…”
Section: Introductionmentioning
confidence: 99%